Subarachnoid Hemorrhage Mimicking Leakage of Contrast Media After Coronary Angiography - Oh, Min Seok (The Korean Society of Cardiology, 2012)
We report a patient who developed subarachnoid hemorrhage (SAH) just after coronary angiography (CAG) with non-ionic contrast media (CM) and minimal dose of heparin. The 55-year-old man had a history of acute ST elevation myocardial infarction that had been treated with primary percutaneous coronary intervention and was admitted for a follow-up CAG. The CAG was performed by the transradial approach, using 1000 U of unfractionated heparin for the luminal coating and 70 mL of iodixanol. At the end of CAG, he complained of nausea and rapidly became stuporous. Brain CT showed a diffusely increased Hounsfield unit (HU) in the cisternal space, similar to leakage of CM. The maximal HU was 65 in the cisternal space. No vascular malformations were detected on cerebral angiography. The patient partially recovered his mental status and motor weakness after 2 days. Two weeks later, subacute SAH was evident on magnetic resonance imaging. The patient was discharged after 28 days.